The lived experience of women studying nursing online in regional, rural and remote areas: an integrative literature review - Keden May Montgomery; Kathie Ardzejewska; Alison Casey; Rosemarie Hogan (BMC Nursing)
Abstract Background There is a critical shortage of registered nurses working in regional, rural and remote Australia. It is the people from these areas that are most likely to address this shortage. This research therefore sets out to explore the question “what is known about the experiences of regional, rural and remote Australian women undertaking a Bachelor of Nursing program delivered online?”. Methods The methodology was an integrative literature review which included: 1) problem identification, 2) literature search, 3) data evaluation, 4) data analysis and 5) conclusion. Articles identified as part of the review explored different aspects of the research question. Results Using thematic analysis, it was possible to extrapolate four interrelating themes: (1) juggling ‘women’s work’ and study, (2) the online learning environment is isolating, (3) the cost of clinical placement, and (4) maintaining overall wellness while studying. Conclusion The literature consistently failed to explore the intersection of the complex challenges facing these students. What is important about this integrative literature review, however, is that the themes identified provide a small and incomplete insight into the experiences of such women, and with a workforce shortage already in play and students continuing to withdraw from their studies, there is a need to find a way to better serve regional, rural and remote Bachelor of Nursing students and their communities.